Effect of health promotion and Whatsapp reminder to self-efficacy of the consumption of Fe tablets adherence among pregnant women - Dyah Tri Kusuma Dewi; Wiwik Kusumawati; Ismarwati Ismarwati (Universitas Aisyiyah Yogyakarta, 2019)
Maternal Mortality Rate (MMR) as an indicator of maternal health during pregnancy, childbirth, and childbirth. Anemia contributes 20% to the incidence of maternal deaths caused by bleeding during labor. The government prevents anemia by giving iron tablets at least 90 tablets for pregnant women. However, the prevalence of anemia remains high, because of the low adherence in consuming Fe tablets every day. Self-efficacy adherence is a predictor of health behavior and adherence to treatment.To improve adherence with self-efficacy in consuming Fe tablets in pregnant women with health promotion and WhatsApp reminder in Yogyakarta City Health Center.This study used a quasi-experiment method with a pre-test post-test non-equivalent control group design. The sample amounted to 59, the sampling technique used was consecutive sampling which was taken by random sampling technique in which samples were taken alternately to determine the intervention group and the control group.There were significant differences in the self efficacy score between the intervention groups (Mean = 6.30, SD = 8.11) and the control group (Mean = 0.89, SD = 7.83) with t-test = 2.60 and ρ = 0.012.There is a significant difference in self-efficacy adherence with consuming Fe tablets in pregnant women before and after being given health promotion and WhatsApp reminder intervention and control groups. Health service agencies can consider the combined service between health promotion and WhatsApp reminder to improve self-efficacy in adhering to consuming Fe tablets in increasing Hb levels in anemic pregnant women.